Organizational justice and its relationship to job involvement in institutions - Chouabbi, Sarra; Ameur, Hicham; Boughari, Fatma Zohra (International journal of economic perspectives, 2024)
The study aimed to identify the degree of correlation between the dimensions of organizational justice and job integration in the Algeria Telecom Corporation in the state of El Tarf, through a field study using the questionnaire that was distributed to a random sample of 50 workers. We used the descriptive analytical approach, and after analyzing the study data through a set of statistical methods using the statistical packages for the social sciences program spss.v22, the following results were found: -The existence of a direct (positive) correlation between the dimensions of organizational justice (distributive justice, procedural justice, transactional justice) and job integration; -The existence of a direct (positive) correlation between the independent variable (organizational justice) and the dependent variable (job integration).